Multi-Spectroscopic Approach for the Non-invasive Characterization of Paintings on Metal Surfaces - Albini, Monica; Ridolfi, Stefano; Giuliani, Chiara; Pascucci, Marianna; Staccioli, Maria Paola; Riccucci, Cristina (Frontiers in Chemistry, 2020)
The aim of this study is to propose a non-invasive multi-spectroscopic approach for the characterization of oil painting artworks that use a copper plates as substrate in place of a canvas. Indeed, in the last decade, many studies have been conducted on artworks made of single materials (e.g. paintings, stones, metals). However, the characterization and conservation of composite artefacts has never be fully investigated even though many masterpieces were created using this particular technique. In this work, several spectroscopic techniques such as Infrared Spectroscopy (FTIR), Energy-Dispersive X-Ray Fluorescence spectroscopy (EDXRF) and high spatial resolution Field Emission Scanning Electron Microscopy coupled with Energy Dispersive X-ray Spectroscopy (EDS), and Optical Microscopy (OM) were performed. The obtained results allowed to fully characterize the micro-chemical and microstructural features of the painted surfaces and of the metal plate. Particularly effective was the use of MA-XRF, resulting in the chemical map of the painted surfaces. Furthermore, traces of the mechanical preparation of the plate were found under the painted layers. Finally, the interface area between the paint film and the metallic support was characterized at a micro scale. This was particularly important in order to identify the degradation products formed by the interaction between the fatty acids of the binder and copper-based substrates.